The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12884-017-1422-5
|View full text |Cite
|
Sign up to set email alerts
|

Causal explanations of miscarriage amongst Qataris

Abstract: BackgroundDespite its commonality, there is a paucity of literature on miscarriage in non-Western societies. In particular, there is little understanding of how people ascribe cause to miscarriage. This research sought to gain an in-depth understanding of notions of miscarriage causality and risk amongst Qataris.MethodsThe study adopted an exploratory descriptive qualitative approach and collected data during 18 months of ethnographic research in Qatar, including semi-structured interviews. The sample includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Unexplained stillbirths at term in maternal diabetes are attributed to maternal hyperglycaemia and foetal hyperinsulinaemia, foetal hypoxia and acidaemia and cardiomyopathy due to glycogen deposition in the myocardium [ 68 , 69 ]. Maternal diabetes has also been associated with an increased risk of miscarriages and habitual abortions [ 70 , 71 ]. Animal models have shown that maternal diabetes affects pre-implantation in the embryo developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Unexplained stillbirths at term in maternal diabetes are attributed to maternal hyperglycaemia and foetal hyperinsulinaemia, foetal hypoxia and acidaemia and cardiomyopathy due to glycogen deposition in the myocardium [ 68 , 69 ]. Maternal diabetes has also been associated with an increased risk of miscarriages and habitual abortions [ 70 , 71 ]. Animal models have shown that maternal diabetes affects pre-implantation in the embryo developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…, 16 , 17 , 18 , 19 , 20 , 21 , 22 Saudi Arabia (n = 5), 23 , 24 , 25 , 26 , 27 Jordan (n = 4), 28 , 29 , 30 , 31 and 3 studies each were conducted in the USA 32 , 33 , 34 and Qatar. 35 , 36 , 37 Two studies were conducted in Palestine, 38 , 39 and one study each was conducted in Canada, 40 Sweden 41 and Turkey. 42 …”
Section: Resultsmentioning
confidence: 99%
“… 12 , 14 , 15. , 16 , 20 , 22 , 27 , 29 , 30 , 31 , 33 , 38 , 40 , 42 Five studies used both interviews and focus groups, 20 , 24 , 36 , 37 , 38 and one study used an 18-month long ethnographic study method. 37 All of the included studies used thematic analysis to evaluate the data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the women of this study attributed the cause of their abortion to God's will. For this reason, religious beliefs can protect women against evil eyes during pregnancy and prevent abortion (32). A woman with the experience of abortion is often considered sinister and thus forbidden to approach young women lest she transfers her evil influence onto the other pregnant women (33).…”
Section: Discussionmentioning
confidence: 99%